1990
DOI: 10.1002/j.1460-2075.1990.tb08079.x
|View full text |Cite
|
Sign up to set email alerts
|

Single islet beta-cell stimulation by nutrients: relationship between pyridine nucleotides, cytosolic Ca2+ and secretion.

Abstract: It is generally believed that the initiation of insulin secretion by nutrient stimuli necessitates the generation of metabolic coupling factors, leading to membrane depolarization and the gating of voltage‐sensitive Ca2+ channels. To establish this sequence of events, the kinetics of endogenous fluorescence of reduced pyridine nucleotides [NAD(P)H], reflecting nutrient metabolism, were compared to those of cytosolic calcium ([Ca2+]i) rises in single cultured rat islet beta‐cells. In preliminary experiments, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
154
1
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(180 citation statements)
references
References 49 publications
(42 reference statements)
23
154
1
2
Order By: Relevance
“…The amounts of both NCAM and integrins have thus been shown to differ from one b-cell to the next (Bosco et al 2000, Bernard-Kargar et al 2001, and functional heterogeneity has been documented by several groups (Salomon & Meda 1986, Stefan et al 1987, Pralong et al 1990, Soria et al 1991, van Schravendijk et al 1992. In the present study, the strongest labeling of E-cadherin was observed in the more central part of islets, corresponding to b-cells that have the higher insulin secretion activity (Stefan et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The amounts of both NCAM and integrins have thus been shown to differ from one b-cell to the next (Bosco et al 2000, Bernard-Kargar et al 2001, and functional heterogeneity has been documented by several groups (Salomon & Meda 1986, Stefan et al 1987, Pralong et al 1990, Soria et al 1991, van Schravendijk et al 1992. In the present study, the strongest labeling of E-cadherin was observed in the more central part of islets, corresponding to b-cells that have the higher insulin secretion activity (Stefan et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of ␤ cells to glucose also leads to increased concentrations of a number of molecules, which may conceivably interact with PAS domains (38) and affect a change in PASK tertiary structure and hence phosphorylation state. These include reduced pyridine nucleotides (39,40), ATP and ADP (11,41), and Ca 2ϩ (42), in addition to a range of glycolytic intermediates, amino acids (43), and fatty acids (44), as well as a decrease in O 2 tension (45) and membrane potential (46). Identification of those parameters that play a role in regulating PASK activity requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…From the effect of D-NAME on both phases of fi cell response to the amino-acid, it can be concluded that a direct depolarizing effect could, again, account for a small part of the potentiation by L-NAME of insulin secretion induced by leucine. This amino acid is not a substrate for NO synthase but a-ketoisocaproate is able within seconds to increase intracellular levels of NADPH and Ca2+ (Pralong et al, 1990); both enzymatic co-factors, allowing an increased NO production, might thereby exert an inhibitory feed-back unmasked by L-NAME administration. Such an hypothesis is supported by the relatively low effectiveness of L-NAME in potentiating tolbutamide and KCl-induced insulin secretions.…”
Section: Discussionmentioning
confidence: 99%